Bio-Detoxification of Spent Ore and Heap Leach Solutions - Leslie C. Thompson; Eric Jones (Society for Mining, Metallurgy & Exploration, 1993)
Biological processes for cyanide detoxification in mine waste are receiving attention as an alternative to conventional chemical treatment options. Some of the advantages of biological treatment include: Low comparative treatment cost * Shorter treatment time * In Situ Treatment * Complete Detoxification - Ends long-term liability - Eliminates in-perpetuity monitoring - Natural Re-Vegetation potential Natural and non-toxic nutrients, by-products and process end-products Hecla Mining chose a bio-neutralization process developed by Pintail Systems, Inc. for cyanide detox in spent are and process solutions from heap leach operations at the Yellow Pine Unit. The Yellow Pine operation is located 50 air miles east of McCall, Idaho, in the Stibnite Mining District. This district is a historic mining district dating back to the early 1900's. During World War II, this district produced a majority of the antimony and tungsten the United States using for the war effort. More recently, the Stibnite district has been known for its gold production. Hecla Mining Company is based in Coeur d'Alene, Idaho, and is a leading domestic producer of precious metals and a major supplier of specialty aggregate and industrial minerals. Pintail Systems, Inc. is a company specializing in the development of biological treatment processes for mine waste remediation. PSI has offices in three states and a laboratory, pilot plant and field office in Aurora, Colorado